Holy waters: an interdisciplinary examination of religion and alcohol - Lemasters, Ryan; Covell, Stephen Grover (Routledge, 2025)
Wine, beer, and drunkenness in the Hebrew Bible, ancient Israel, and biblical scholarship / Rebekah Welton -- Again you will plant vineyards: prophecy, Jewish settlement, and temporal dissonance in the occupied West Bank / Ian McGonigle -- Cultural enology: what wine can teach us about religion (and about Jewish Kabbalah and Hasidism in particular) / Vadim Putzu.